Analisis Wacana Kritis Dalam Wacana Humor Abdurrahim Arsyad Stand Up Comedy 4 (Suci 4) Di Kompas TV - Wulandari, Dewi Asri (2016)
The research aims at describing analysis of critical discourse, comic's and audience's perception, and the analysis is based on the content of Abdurrahim Arsyad's humor discourse of Stand Up Comedy 4 (SUCI 4) on Kompas TV. Qualitative descriptive method. The data sources are interview and video transcript of Abdurrahim Arsyad and interview of audiences of Stand Up comedy 4 (SUCI 4) on Kompas TV. The data collection techniques are reading, screening, and recording. The validity of data uses triangulation theory and data triangulation, analyzing data uses referential unified method with analysis technique of interactive data model and discourse analysis. The research shows about the usage of power rights, politicians are more concerned with elite political and party member issues than issues of public interests. Abdur also critizes government toward discrimination eastern people and social issues and disappointment toward government upon eastern people who lack of government's attention. Moreover, he also critizes on education, infrastructure, social needs, information technology, social gap issues. Indonesian people who do not care with their arts and cultures, low achievement at sports, and lack of government aids toward social health at isolated village. The context as a comic who cannot hinder Abdur's background life leads society to reveal social problems. The perception of Abdur and audiences are that humor discourse of Abdur has something which can arouse audience interest, not only for entertainment, but also for a message to make them pay more attention upon their environment around them.